Ex vivo sentinel lymph node investigation in colorectal cancer - Freitas,Antônio Hilário Alves (2013)
INTRODUCTION: In Brazil, about 26,000 cases of colorectal cancer are diagnosed per year. Patients considered at the early stage of disease (without lymph node) evolve with tumor relapse or recurrence in up to a quarter of cases, probably due to understaging. Objective: Research on ex vivo sentinel lymph node in patients with colorectal adenocarcinoma. MATERIALS AND METHODS: We studied 37 patients who underwent curative surgical resection. The marker used to identify lymph nodes was patent blue dye injected into the peritumoral submucosa of the open surgical specimen immediately after its removal from the abdominal cavity. RESULTS: Ex vivo identification of sentinel lymph node with marker occurred in 13 (35.1%) patients. The sensitivity was 40% and 60% false negative. The detailed histological examination of sentinel lymph nodes with multilevel section and immunohistochemistry showed metastasis in one (4.3%) individual, considered ultra-staging. CONCLUSION: The ex vivo identification of sentinel lymph node had questionable benefits, and worse results when include patients with rectal cancer. Restaging of one patient was possible after multilevel section and immunohistochemistry of the sentinel lymph node, but more research is needed to evaluate the role of micrometastases in patients with colorectal cancer.